CORRELATION OF THE LATE CENOZOIC ENDOGENIC EVENTS AND CLIMATIC VARIATIONS IN CENTRAL ASIA - Yarmolyuk V.V.; Kuzmin M.I. (My University, 2006)
Trend of climatic changes in geological history of the Earth was determined by gradual decrease in the global surface temperature. Substantial deviations from this trend depended on the prevalent type of volcanism: predominantly explosive volcanism at convergent boundaries between lithospheric plates led to cooling and onset of glacial epochs, while intense intraplate volcanism strengthened greenhouse effect and resulted in global warming. During cold epochs, orogenic processes played an important role in climatic variations. The most frequent and regular climatic variations are controlled by the Earth position in solar orbit (Milankovitch cycles). The Late Cenozoic variations of cold climate were interrelated with orogenic processes caused by collision between the Indian and North Asian lithospheric plates. The first event of considerable cooling in the Northern Hemisphere (2.8-2.5 Ma ago) coincided with a rapid growth of mountains throughout the collision belt. The Tibetan Plateau formed in South Asia. In Central Asia, the large (> 1.5 × 106 km2) Khangai-Altai-Sayan mountain system appeared 3 Ma ago. Total area subjected to orogenic processes in Central and South Asia exceeded 9 × 106 km2. The intense intraplate volcanism suggests that sublithospheric mantle was involved into orogenic processes. Alternation of glacial and interglacial climatic epochs during the last 1.8 m.y. is recorded in Central Asia. These climatic variations are compatible with the Milankovitch cycles. As is established, climatic events recognizable in the Baikal sedimentary record are correlative with interglacial and glacial epochs detectable in volcanic lavas of the East Sayan Mountains. There are indications of lava eruptions into ice during the cold periods. It is assumed therefore that all the cooling epochs detectable in the Baikal sedimentary record after 1.8 Ma were associated with development of mountain glaciation that formed glacial sheet up to 3 km thick and 100000 km2 in size. During the Brunhes Chron, there were eight glaciations at least. The endogenic (volcanism and orogeny) and exogenic (glaciation) processes during the last 3 m.y. are shown to be correlative. The intermittent development and degradation of thick ice sheets was responsible for oscillation of lithospheric load on the asthenosphere, and this caused periodical magma generation in marginal parts of volcanic provinces. © MAIK "Nauka/Interperiodica" 2006.
Keywords: CLIMATE; INDIA-ASIA COLLISION; K-AR DATING; OROGENY; RECENT VOLCANISM